2003
DOI: 10.1046/j.0818-9641.2002.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages of patients with X‐linked thrombocytopenia display an attenuated Wiskott‐Aldrich syndrome phenotype

Abstract: SummaryThe immunodeficiency disorder Wiskott-Aldrich syndrome and its milder form X-linked thrombocytopenia are caused by mutations in the WASp gene. Wiskott-Aldrich syndrome is characterized by a plethora of clinical symptoms which are due to functional defects of haematopoietic cells, including the inability of macrophages to form actin-rich adhesion structures called podosomes. In contrast, X-linked thrombocytopenia patients show reduced platelet size and counts but no cytoskeletal white blood cell defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…XLT patients express the mutant WASPs at a lower concentration than normal subjects, and the defects are observed only in platelets and not in other hemopoietic cells (43)(44)(45)(46)(47)(48). Recently, Linder et al reported that XLT macrophages, previously thought to be unaffected in this disorder, are compromised in podosome formation (49). Complex formation of mutant WASPs with WIP is impaired in XLT patients, because XLT mutations reduced WASP binding to WIP (50).…”
Section: Discussionmentioning
confidence: 99%
“…XLT patients express the mutant WASPs at a lower concentration than normal subjects, and the defects are observed only in platelets and not in other hemopoietic cells (43)(44)(45)(46)(47)(48). Recently, Linder et al reported that XLT macrophages, previously thought to be unaffected in this disorder, are compromised in podosome formation (49). Complex formation of mutant WASPs with WIP is impaired in XLT patients, because XLT mutations reduced WASP binding to WIP (50).…”
Section: Discussionmentioning
confidence: 99%
“…XLT patients express the mutant proteins at a lower concentration than normal subjects (3,4,61,62), and defects were observed in only platelets, but not in other hemopoietic cells (3,4). Recently, Linder et al (57) reported that XLT macrophages, previously thought to be unaffected in this disorder, are compromised in podosome formation. Complex formation of mutant WASPs with verprolins is most likely impaired in XLT patients, because XLT mutations reduced WASP binding to WIP (56).…”
Section: Discussionmentioning
confidence: 99%
“…The SH3 domain of CIP4 interacts with Wiskott-Aldrich syndrome protein, a regulator of the actin cytoskeleton, whereas the amino-terminal region including the FCH domain binds to microtubules, suggesting that CIP4 is a potential linker between the actin cytoskeleton and microtubules (27). Actually, CIP4 has been shown to be involved in microtubule-dependent formation of F-actin-rich podosomal adhesion in macrophages (30). Rapostlin has two functional domains, FCH-containing amino-terminal region and SH3 domain, those of CIP4 being involved in the reorganization of both microtubules and actin filaments.…”
Section: Discussionmentioning
confidence: 99%